Aceptación de anticonceptivos durante el puerperio en embarazos no planeados. - Romero Gutiérrez, Gustavo; Ofelia Soria Villanueva, Susana; Lilia Ponce Ponce de León, Ana (Ginecología y Obstetricia de México, 2009)
Background: In spite the high rate of contraceptives use, the unplanned pregnancies still frequently occur. It is unknown the amount of women with unplanned pregnancies who accept contraceptive methods at immediate postpartum. Objective: To determine the frequency of women with unplanned pregnancies who accept contraceptives at immediate postpartum and the associated factors with its acceptance. Material and method: In a cross-sectional study, women at immediate postpartum were recruited. They were asked if their pregnancy was planned or unplanned; if at postpartum accepted some contraceptive method and reasons for acceptance or not. The statistical analysis included arithmetic mean, standard error, percentages, χ², Student t test; and logistic analysis regression for determining the associated factors with the acceptance of contraceptives. An alpha value was set at 0.05. Results: Of 1,024 women 566 (55.3%) had a planned pregnancy and 457 of them (80.7%) accepted contraceptives. The remaining 458 women (44.7%) had an unplanned pregnancy and 402 (87.8%) accepted contraceptives, p = 0.003. The significant factor associated with the acceptance of contraceptives was the multiparity, p = 0.034. Conclusion: There is more acceptance of contraception in women with unplanned pregnancy. In these women the multiparity is associated with higher acceptance of contraceptive methods. It is recommended to reinforce the contraceptive counselling in this group of women.